The Varieties of Money Laundering and the Determinants of Offender Choices - Riccardi, Michele (European journal on criminal policy and research, 2024)
Two images dominate discussion of money laundering. Investigative journalists and politicians stress the variety and sophistication of methods that have been used to launder money of corrupt officials and white collar offenders. The research literature, largely dependent on criminal cases, emphasizes how unsophisticated and routine are the laundering methods used by drug dealers and other illegal market participants. The discrepancy may reflect the incapacity of police to detect sophisticated money laundering but it may also represent the reality; different groups of offenders choose different methods. This paper presents a theoretical framework to explain how offenders choose to launder their criminal earnings. Specifically it asks: what determines the sophistication of the method chosen? Among the variables that we suggest influence the choice are: (a) the type of predicate crime and of crime proceeds, (b) the type of offender (age, education, social status), (c) his/her motivations, (d) the AML environment and the level of AML controls. The paper provides arguments from criminological and economic theory for how these variables might play a role. Without claiming that individual cases can test the theory, we offer some case narratives to suggest the plausibility of the factors that we propose.